X-Rays and their Applications in the Medical Field - Ajil, Hussein Hadi Faraj; Hussein, Haider Hussein Ali Abdel; Hadi, Benin Ali; Mohammed Ali, Nabaa Hussein Hekmit (American Journal of Botany and Bioengineering, 2024)
We learned about x-rays, who is the inventor of x-rays, and why was he called by this name. We also know the uses of materials used in medicine to make X-ray images of The target of the research bones and internal organs of the body and In the treatment of cancer, as they kill cancer cells easier than killing normal cells. -In industry, X-rays are used to examine products made of different types of materials, including aluminum, steel and other metals, and reveal radiological images For cracks and other defects in these products that do not appear on the surface, and are also used In airports to search for weapons in luggage and in scientific research, X-rays have been used to analyze the arrangement of atoms in many types of materials especially crystals, and the organization of atoms In crystals at Levels separated by regular distances.We also learned about the properties of x-rays and how the x-rays are created in a tube called a sweep tube made of threads made of tungsten wire. We touched on how to detect x-rays and what are the components of the x-ray device .and some of Its types and specifications.